Paradigm Of New Institutional Administrations in The Governance and Institutionalization of Marine Tourism in Payangan, Indonesia - HS, M Hamdi; Soepeno, Bambang; ., Supranoto; Suryawati, Dina (International Journal of Membrane Science and Technology, 2023)
Marine tourism management is not just a matter of governance per se, institutional factors also seem to have an influence, especially in traditional marine tourism management, such as in Payangan. To understand the relationship between governance and institutions in marine tourism management in Payangan, this study aims to analyze the problems in governance and institutions in Payangan, as well as to develop a conceptual model design. The method used in this research is a qualitative method with the Soft System Methodology (SSM) approach as a systemic approach to solve complex governance and institutional problems in Payangan through a series of stages. The research results indicate that the dominant problem situation in Payangan is not in its governance, but rather in its institutions, particularly in accommodating the values of the local community that have long been neglected, as they are monopolized by certain small community groups and elements of the Sumberejo Village Government who are only seeking economic gain. The monopolies of certain parties have caused the governance and institutionalization of marine tourism in Payangan to not function properly, requiring a new conceptual model of governance and institutions based on the construction of reality, social networks, and path-dependent development within the realm of the science of administration, or New Institutional Administrations (NIA), as a development and critique of the first-level institution or embeddedness proposed by Williamson, which has economic dimensions or New Institutional Economics (NIE).